Tin Decorated Zinc Sulphide Nanoparticles for Photocatalytic Degradation of Bromophenol Blue Dye and Their Therapeutic Applications: A Kinetic and Thermodynamic Approach. (1st March 2022) - Shah, Umar; Jan, F. Akbar; Ullah, Rahat; Wajidullah,; Salman,; Ullah, Naimat
Abstract : Zinc sulphide (ZnS) and Tin doped Zinc sulphide (Sn-ZnS) nanoparticles (NPs) were synthesized by co precipitation method. The synthesized NPs were characterized using UV–vis spectroscopy, X-ray diffraction (XRD), Energy dispersive X-ray analysis (EDX), Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), Thermo gravimetric analysis (TGA) and Photoluminescence (PL) spectroscopy. With the addition of 3% tin the band gap of ZnS reduced from 3.50 eV to 3.10 eV which confirmed successful doping. XRD study showed cubic crystal structure of the synthesized material while SEM study confirmed that Sn-ZnO NPs have spherical surface morphology. TGA study revealed that the synthesized NPs are much stable to temperature and only 22.8% and 21.5% weight loss occurs in ZnS and Sn-ZnS nanocatalys respectivelyt. The photoluminescence (PL) intensity showed that with Sn doping peak in Sn-ZnS shifted to longer wavelength required lesser energy for excitation. The degradation of Bromophenol blue over both the catalysts followed first order kinetics. The activation energy calculated for the photodegradation reaction was 53.2kj mol −1 and 67.55kj mol −1 using pure ZnS and Sn-ZnS NPs respectively. About 86% and 96% dye degradation was observed in 300 min time duration. High percent degradation was found at low dye concentration (10ppm) and at optimal dosage (0.03 g) of the catalyst. The rate of dye degradation was found to increases with increase in temperature (upto 70 °C) and pH(9.5) of the medium. The recyclability study showed that both pure ZnS and Sn-ZnS NPs could be reused for the degradation of the given dye. Sn-ZnS NPs showed good antibacterial and antioxidant activities as compared to bare ZnS. Both the nanoparticles are found to be non biocompatible.